2021
DOI: 10.1111/joes.12448
|View full text |Cite
|
Sign up to set email alerts
|

Political connection, contract intensity, and OFDI: Evidence from China

Abstract: A typical feature of business-government relationships in China is that many Chinese firms have politically connected managers or board members; thus, these firms have greater access to privileges and resources in the domestic market. In this context, we examine how this domestic political connection affects firms' greenfield investments. We first present a simple heterogeneous firm framework by incorporating political connections and contract enforcement into a monopolistic model. The theoretical proposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…In the absence of officially available data, the reasons for using our constructed city-level OFDI data are as follows: (1) After the “going globally” strategy, the listed companies have become the major participants in Chinese overseas investment activities (Chen et al 2016 ; Guo et al 2022 ). Going with that, we mainly use overseas investments from the listed companies to construct city-level OFDI data and then apply some OFDI-related information from non-listed companies and the official government websites to assist.…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of officially available data, the reasons for using our constructed city-level OFDI data are as follows: (1) After the “going globally” strategy, the listed companies have become the major participants in Chinese overseas investment activities (Chen et al 2016 ; Guo et al 2022 ). Going with that, we mainly use overseas investments from the listed companies to construct city-level OFDI data and then apply some OFDI-related information from non-listed companies and the official government websites to assist.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have suggested that investment policies are a function of multiple independent factors (Chen and Ma, 2017;Guo et al, 2021). At the macro level, studies have analysed the investment environment impacts on CB M&A decisions, such as marginal tax rates and external regulations (Gubbi et al, 2010;Kolstad and Wiig, 2012;Yang et al, 2016;Liu et al, 2017;Tian and Yu, 2017;Guo et al, 2021). At the micro level, studies have tended to focus on CB M&A growth opportunities, financing capabilities, and monopoly advantages (Dunning and Lundan, 2008;Min and Liu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al. (2021) examine the effect of the Chinese domestic business‐government relationship on firms’ expansion strategy. A typical feature of this relationship in China is that firms with more politically connected managers or board members have better access to domestic privileges and resources.…”
mentioning
confidence: 99%